Effectiveness of mHealth on self-care profile and blood pressure among patients with hypertension in Indonesia: A single-blind randomized controlled trial - Widyastuti, Chatarina Setya; Dinarti, Lucia Kris; Aulawi, Khudazi; Lazuardi, Lutfan (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: Self-management is essential for controlling blood pressure and requires consistent effort. Mobile health (mHealth) applications can support patients in independently managing hypertension and maintaining better control over their blood pressure. Objective: This study aimed to evaluate the effectiveness of MaRiTensi mobile application in improving knowledge, motivation, self-efficacy, and self-care among patients with hypertension, as well as in lowering blood pressure. Methods: A two-arm randomized controlled trial with a single-blind evaluator was conducted among 108 patients with hypertension, recruited from a private hospital and two health centers in Yogyakarta, Indonesia. The 12-week study was implemented from October 2023 to April 2024. Participants were randomly assigned to the intervention group, which used the MaRiTensi app, or the control group, which received usual care. Primary outcomes—knowledge, self-care, self-efficacy, and motivation—were measured using a validated questionnaire, while the secondary outcome—blood pressure—was assessed through clinical measurement. Ninety-nine participants completed the study and were included in the analysis. Repeated measures ANOVA was used to evaluate within-group changes over time. Intergroup comparisons were analyzed using the chi-square test, independent t-test, or Mann–Whitney U test. Results: No significant baseline differences were found between the two groups (p >0.05). Significant improvements were observed in knowledge, self-care, and systolic and diastolic blood pressure in both groups (p <0.01). Self-efficacy significantly improved only in the intervention group (p <0.01). No significant changes in motivation were observed over time in either group (p >0.05). Significant between-group differences were found at the first evaluation for self-care (p = 0.005; d = 0.58), self-efficacy (p = 0.011; d = 0.52), motivation (p = 0.026; d = 0.44), systolic pressure (p = 0.039; d = 0.42), and diastolic pressure (p = 0.009; d = 0.54), and at the second evaluation for self-care (p = 0.024; d = 0.46). Conclusions: MaRiTensi may effectively improve self-care, self-efficacy, and blood pressure control among patients with hypertension, although it showed limited impact on knowledge and motivation. The application shows promise as a nursing intervention, but further research is needed to assess its long-term effectiveness and sustainability. Trial Registry Number: NCT06049862 [ClinicalTrials.gov]